Longitudinal Effects of an Intergenerational mHealth Program for Older Type 2 Diabetes Patients in Rural Taiwan. Issue 2 (April 2020) - Yu, Kexin; Wu, Shinyi; Lee, Pey-Jiuan; Wu, Du-An; Hsiao, Hsin-Yi; Tseng, Yi-Chuan; Wang, Ying-Wei; Cheng, Ching-Feng; Wang, Yi-Hsuan; Lee, Szu-Pei; Chi, Iris
Purpose: The purpose of the study is to test the longitudinal efficacy of a mHealth intervention (Intergenerational Mobile Technology Opportunities Program, IMTOP) for older type 2 diabetes mellitus (T2DM) patients in rural Taiwan. Few mHealth programs targeted rural older adults and the longitudinal effects are unknown. Methods: Ninety-seven T2DM patients aged 55+ were recruited from an outpatient in Hualien, Taiwan. The intervention comprised 8-week technology and diabetes self-management training and 4-week technical support. College student tutors facilitated T2DM patients to learn technology. Participants used a diabetes self-management app to track health behaviors. Outcomes measured at baseline and at 4 and 8 months including patient-reported self-care behaviors, T2DM symptoms, clinical outcomes, health resource utilization, and medical expenditure. Linear mixed-effect regressions of repeated measures were conducted for each outcome. Results: At 4 months, improvements in self-care behaviors were reported in diet, exercise, smoking, and blood glucose testing. Patients paid less endocrinology clinic visits, spent less on endocrinology medications, and improvements in fasting blood glucose and total cholesterol were observed. At 8 months, the statistical significance of improvements in diet and smoking were maintained, and the averaged endocrinology clinic visits remained less than baseline. However, more frequent occurrence of diabetes symptoms were reported at both follow-ups. Conclusions: IMTOP had lasting effects on diet and decreased smoking behavior, clinic visits, and medication costs over 8 months. Self-monitoring through an app increased awareness and may explain the increased reporting of diabetes symptoms. IMTOP is a promising model for promoting T2DM self-management in rural areas.